Graduate students' critical thinking disposition and emotional intelligence: a pilot study - Kang, Fong Luan (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This study assessed the present level of critical thinking disposition and emotional intelligence of graduate students, followed by the exploration of their relationship. The differences in gender and course of study on these two variables were also examined. A total of 60 graduate students from the Faculty of Educational Studies, Universiti Putra Malaysia (UPM) completed the self-administered structured questionnaires. Findings suggested that the graduate students have moderate critical thinking disposition and emotional intelligence. Additionally, there was a significant strong positive correlation (r=.619) between critical thinking disposition and emotional intelligence of graduate students. However, there were no significant differences in gender and course of study on critical thinking disposition and emotional intelligence of graduate students. Generalization was however limited to the educational studies graduate students and the variables under study merely described the values that respondents ascribed to, not actual behaviors.